2017
DOI: 10.1007/s11356-016-8123-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term impact of reduced tillage on water and pesticide flow in a drained context

Abstract: Influence of more than 20 years (1988-2010) of reduced tillage (RT) practices on water and pesticide balances and dynamics is analyzed and compared to results from a conventional tillage plot (CT). The field study soils are described as silty clay stagnic luvisol, developed on a low permeable schist layer. A drainage network was set up according to French criteria (0.9 m deep, 10 m space) to avoid soil winter waterlogging. Climate is temperate oceanic and drainage generally occurs from November to March. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Reducing tillage intensity can help mitigate soil erosion and generally improves biological and physical soil health. If coupled with cropping system diversification NT can increase SOM, AS, biological activity, connectivity of soil pores and permeability [3,12,15,[20][21][22]. However, those responses are not consistent as reflected in other studies that have reported soil structure degradation under NT.…”
Section: Introductionmentioning
confidence: 75%
“…Reducing tillage intensity can help mitigate soil erosion and generally improves biological and physical soil health. If coupled with cropping system diversification NT can increase SOM, AS, biological activity, connectivity of soil pores and permeability [3,12,15,[20][21][22]. However, those responses are not consistent as reflected in other studies that have reported soil structure degradation under NT.…”
Section: Introductionmentioning
confidence: 75%
“…Reduced-and no-tillage have been widely adopted to reduce soil erosion and are currently used worldwide on approximately 150 million hectares (Kassam et al 2015). No-tillage has also been incorporated into several conservation practices, adapted to increase crop diversification, and shown to improve soil health and provide both environmental and economic benefits (Kassam et al 2015, Dairon et al 2017. It has also been identified (FAO (2016)) as an important soil management component of conservation agriculture, but NT is not without its challenges and improvements are needed to expand its adoption and capture its societal benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Conservation and reduced tillage practices were initiated in the United States to reduce soil erosion following the 1930s Dust Bowl, but adoption is still below 40% in most states (CTIC, 2019). An important driver for soil health is that in addition to reducing soil erosion, decreased tillage intensity can also improve physical and biological soil properties (Dairon, Dutertre, Tournebize, Marks‐Perreau, & Carluer, 2017; Nunes, Karlen, Veum, Moorman, & Cambardella, 2020). However, effects of tillage intensity on chemical soil health indicators (i.e., soil pH and nutrients) within the profile are still uncertain because of potential accumulation at or near the soil surface and depletion within subsurface layers (Deubel et al., 2011; Noack et al., 2014; Nunes et al., 2019).…”
Section: Introductionmentioning
confidence: 99%